A new method of carrier density measurement using photocurrent maps of a 2D material Schottky diode - Ahn, Il-Ho; Ahn, Jongtae; Hwang, Do Kyung; Kim, Deuk Young (Elsevier BV, 2021)
A simple method for obtaining the charge carrier density of two-dimensional (2D) materials is proposed herein. A formula is suggested for the extraction of the 2D charge carrier density using the horizontal depletion width, which is visually represented by photocurrent mapping methods. An example of this method is demonstrated using a MoS2 Schottky diode. The results suggest that this method can be useful for a basic analysis of the physical properties of 2D devices.